Pengaruh Biosaka Berbahan Dasar Limbah Pertanian Terhadap Pertumbuhan dan Produktivitas Tanaman Sawi Putih (Brassica rapa) - Destien Atmi Arisandy; Linna Fitriani (Pro-Life, 2024)
This research aims to overcome the problem of agricultural waste, the lack of fertilizer which is really needed by agricultural groups by utilizing agricultural waste into Biosaka fertilizer which can be used sustainably for agriculture. This research is expected to increase the growth and productivity of farmers' vegetable crops, namely white mustard (Brassica rapa). This research is a type of quantitative descriptive research with an experimental method using a Completely Randomized Design (CRD). Analysis of research data with Analysis of Variance (ANOVA) calculated using the SPSS program. The growth observed was plant height and number of leaves as well as the wet weight of white mustard plant products. Based on data from research that has been carried out, data was obtained that the P4 treatment, namely giving 80% biosaka to white mustard plants, showed the best results compared to other treatments. The conclusion obtained is that there is an effect of giving Biosaka on the growth and productivity of white mustard plants (Brassica rapa). Keywords: Biosaka, Brassica rapa